[Verzameling liederen] [Bladmuziek]. ([S.l].)
Deze brochure bevat volgende liederen
Ernst Busch in Paris
Lied der Moorsoldaten
Ballade der XI. Brigade
Die Thälmannkolonne
Hans Beimler
Das Bataillon Edgar André
Mamita mia
Nederlands
Duits
Brochure
Keywords: liederen